The Effect of The Debate Method in Learning Arabic on The Improvement of Student’s Listening and Speaking Skills - Ade Nandang S; Nanang Kosim; Nopri Dwi Siswanto (Gunung Djati Conference Series, 2023)
This research is based on students' prolematics in learning Arabic. Most students have not paid much attention to Arabic material. This causes their weak ability to listen and speak. And that leads to delays in achieving the goals of listening and speaking skills themselves. Judging from the monthly average score of students, as many as 37.5% of students got scores above the KKM on listening skills. Then as many as 45% of students scored above the KKM on speaking ability. The remaining 62.5% of students who scored below the KKM on listening skills, and 55% of students who scored below the KKM on speaking ability. Based on the results of the author's observations in the field, language learning methods Arabic used by teachers in teaching has not been effective, especially in improving listening and speaking skills at Al-Basyariyah Islamic Boarding School Bandung. The debate method is a method that uses thoughts and ideas between two opposing camps that reinforce each other's arguments. There are three terms that must be understood correctly, namely the method approach, and the model in teaching. Listening ability is a person's ability to understand words or sentences spoken by someone or heard through audio. Speaking ability is the ability to express the sounds in a sentence. related ideas conveyed and responding to the statements of others.The purpose of this study was to determine the students' listening ability in learning Arabic, and also to determine their speaking ability in learning Arabic, and to determine the effect of using the debate method on students' listening and speaking skills. The method used in this study was the true experimental design method. And the approach used in this research is a quantitative approach. The data collection method in this study was carried out by direct observation, personal interviews, and tests.The results of this study are that the students' listening ability before using the debate method in Arabic learning shows a good level, this is indicated by an average score of 71. The students' listening ability after using the debate method in Arabic learning shows a very good level, with the average value is 87. While the students' speaking ability before using the debate method in Arabic learning shows a good level, this can be seen in the results of the score with a percentage of 47% while the students' speaking ability after using the debate method shows very good results, This can be seen in the results of the value with a percentage of 66%. The use of the debate method has an effect on the listening ability of experimental class students as much as 0.6, there is an increase of 58%. For the experimental class speaking ability of 0.4, there was an increase of 37%. And as a comparison balance for the control class on listening skills of 0.4, there is an increase of 41%. And in students' speaking ability as much as 0.1 there is an increase of 12%. It can be concluded that the use of the debate method to determine the improvement of students' listening and speaking abilities is very effective compared to students who do not use the debate method (control class).